Characterization of in vitro effects of patulin on intestinal epithelial and immune cells. (27th May 2016) - Assunção, R.; Alvito, P.; Kleiveland, C.R.; Lea, T.E.
Highlights: PAT affected Caco-2 barrier function by perturbation of ZO-1 levels. Phosphorylation of MLC2 accompanied PAT barrier function perturbation. Low doses of PAT inhibited T cell proliferation induced by a polyclonal activator. No effects on the maturation of moDCs were detected. Abstract: The intestinal mucosa is the first biological barrier encountered by natural toxins, and could possibly be exposed to high amounts of dietary mycotoxins. Patulin (PAT), a mycotoxin produced by Penicillium spp. during fruit spoilage, is one of the best known enteropathogenic mycotoxins able to alter functions of the intestine (Maresca et al., 2008 ). This study evaluated the effects of PAT on barrier function of the gut mucosa utilizing the intestinal epithelial cell model Caco-2, and scrutinized immunomodulatory effects using human peripheral blood mononuclear cells (PBMC) and human blood monocyte-derived dendritic cells (moDCs) as test systems. PAT exposure reduced Caco-2 cell viability at concentrations above 12 μM. As expected, the integrity of a polarized Caco-2 monolayer was affected by PAT exposure, as demonstrated by a decrease in TER values, becoming more pronounced at 50 μM. No effects were detected on the expression levels of the tight junction proteins occludin, claudin-1 and claudin-3 at 50 μM. However, the expression of zonula occludens-1 (ZO-1) and myosin light chain 2 (MLC2) declined. Also, levels of phospho-MLC2 (p-MLC2) increased after 24 h of exposure to 50 μM of PAT. T cell proliferation was highly sensitive to PAT with major effects for concentrations above 10 nM of PAT. The same conditions did not affect the maturation of moDC. PAT causes a reduction in Caco-2 barrier function mainly by perturbation of ZO-1 levels and the phosphorylation of MLC. Low doses of PAT strongly inhibited T cell proliferation induced by a polyclonal activator, but had no effect on the maturation of moDC. These results provide new information that strengthens the concept that the epithelium and immune cells of the intestinal mucosa are important targets for the toxic effects of food contaminants like mycotoxins.